Advances in Human Factors in Communication of Design : Proceedings of the AHFE 2019 International Conference on Human Factors in Communication of Design, July 24-28, 2019, Washington D.C., USA /: Proceedings of the AHFE 2019 International Conference on Human Factors in Communication of Design, July 24-28, 2019, Washington D.C., USA. (2019) - Unknown
No abstract available